2021
DOI: 10.1088/1755-1315/917/1/012021
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and challenges for land use-based peatland restoration in Kayu Labu Village, South Sumatra, Indonesia

Abstract: Restoration of degraded peatland has proven to be complex and many activities that have been initiated in recent years have not had a significant impacted on restoring peatland condition. Revitalization activities that have been carried out in several locations have not been effective. Likewise, rewetting actions were often poorly understood by the community. This research aimed to analyze land use-based peatland restoration opportunities and challenges in Kayu Labu village, South Sumatra. Survey methods and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…The abovementioned 4Rs approach aims to serve as a model for the formulation of the peatland restoration activities in Indonesia, although the recently published literature on Indonesia (Lestari et al 2021; Yuwati et al 2021), Indonesian governmental officials (IFAD 2021), and guidelines developed by Malaysia on oil palm plantation restoration (Parish et al 2019) still refer to the 3Rs as the guiding approach when presenting Indonesia's restoration efforts, evidence that awareness on the 4Rs approach is not sufficient or that the approach is not widely recognized by policy makers, researchers and practitioners. Nonetheless, the 3Rs and 4Rs approaches are the only attempts found in the literature at defining elements of peatland restoration interventions.…”
Section: Restoration Of Peat Swamp Forests In Degraded Sites: Guiding...mentioning
confidence: 99%
See 2 more Smart Citations
“…The abovementioned 4Rs approach aims to serve as a model for the formulation of the peatland restoration activities in Indonesia, although the recently published literature on Indonesia (Lestari et al 2021; Yuwati et al 2021), Indonesian governmental officials (IFAD 2021), and guidelines developed by Malaysia on oil palm plantation restoration (Parish et al 2019) still refer to the 3Rs as the guiding approach when presenting Indonesia's restoration efforts, evidence that awareness on the 4Rs approach is not sufficient or that the approach is not widely recognized by policy makers, researchers and practitioners. Nonetheless, the 3Rs and 4Rs approaches are the only attempts found in the literature at defining elements of peatland restoration interventions.…”
Section: Restoration Of Peat Swamp Forests In Degraded Sites: Guiding...mentioning
confidence: 99%
“…timber) transport and local community mobility have been reported in Central Kalimantan (Harrison et al 2019) when communities were not involved in the planning and implementation of rewetting activities. Another study in South Sumatra, Indonesia, found that rewetting activities (R1) undertaken by BRG have not had a significant impact restoring peatlands (Lestari et al 2021). These activities were often poorly understood by local communities, attributable to the fact that local community were not widely engaged in the activities.…”
Section: Proposed Community‐led Restoration Approach: 5rs Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The updated data shows that the peatland in Indonesia covers about 13.43 million ha, distributed in four main islands, Sumatra/5.85 million ha, Kalimantan/4.54 million ha, Papua/3.01 million ha and, Sulawesi/0.024 million ha [2]. Tropical peatland is fragile and has unique physical, chemical, and biological characteristics that differ from mineral land with significant functions in hydrology, ecosystem, biodiversity conservation, and livelihoods [3][4][5][6][7][8][9][10][11]. This condition put tropical peatland degradation in Indonesia as an emerging issue and the main challenge to sustainable peatland management.…”
Section: Introductionmentioning
confidence: 99%
“…However, research on the participation of farmers working on peatlands is limited. One of the studies on farmer participation in the BRG program showed that the program had no impact on people's lives (Lestari et al, 2021). Ideally, the BRG program grows and develops from the community and is carried out consciously by the community, and the results can be perceived by the whole community (Adawiyah & Ramadhan, 2020).…”
Section: Introductionmentioning
confidence: 99%